A Dimeric Calcium-modulated GC-linked Receptor Kinase, PSKR1 - Muleya, Victor; Wheeler, Janet I; Ruzvidzo, Oziniel; Kwezi, Lusisizwe; Thomas, Ludivine; Marondedze, Claudius; Gehring, Christoph; Irving, Helen R (Melbourne Protein Group Student Symposium, 2016)
Abstract